2022
DOI: 10.1111/desc.13310
|View full text |Cite
|
Sign up to set email alerts
|

The relation between aggression and theory of mind in children: A meta‐analysis

Abstract: Previous findings on the association between theory of mind (ToM) and aggression in children are mixed. The social skills deficit view regarded ToM as a single‐edged sword and proposed that a lack of ToM can lead to aggression, while the double‐edged sword view proposed that children with advanced ToM can still show much aggression because children can also leverage ToM to harm others. To resolve the dispute between the two views, we conducted a meta‐analysis combining cross‐sectional and longitudinal findings… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 189 publications
0
2
0
Order By: Relevance
“…In the same vein, people who are able to understand emotions and put themselves in the place of others are less aggressive because of their emotional sensitivity and the possibility of understanding the potential negative consequences that can result from aggression (Cuello and Oros, 2013). Therefore, this construct appears negatively related to aggressive behaviour (although it is not observed in the same way in aggressive behaviours that include bullying, see Wang et al, 2023), and positively related to prosocial behaviour (García-Sancho et al, 2016).…”
Section: Emotional Understanding and Its Relationship To Aggressionmentioning
confidence: 93%
“…In the same vein, people who are able to understand emotions and put themselves in the place of others are less aggressive because of their emotional sensitivity and the possibility of understanding the potential negative consequences that can result from aggression (Cuello and Oros, 2013). Therefore, this construct appears negatively related to aggressive behaviour (although it is not observed in the same way in aggressive behaviours that include bullying, see Wang et al, 2023), and positively related to prosocial behaviour (García-Sancho et al, 2016).…”
Section: Emotional Understanding and Its Relationship To Aggressionmentioning
confidence: 93%
“…Furthermore, research has shown a consistent negative relationship between aggression and ToM. In particular, Wang et al's [26] recent meta-analysis found that, with the exception of bullying, ToM was negatively associated with all forms of aggression. Similarly, Baker et al [27] showed the moderating role of ToM in both physical and relational aggression when comparing children from different socio-economic backgrounds, and Olson et al [28] reported a negative association between aggression and ToM.…”
Section: Conceptualisations 141 Aggression and Victimisationmentioning
confidence: 96%